PENGARUH PERILAKU PHUBBING TERHADAP INTERAKSI SOSIAL PADA SISWA SMAN 1 LUHAK NAN DUO - Arini Zahara; Elviana; Sri Hartati; M. Arif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the existence of phubbing behavior, which results in negative feelings, feelings of disrespect, and disruptions to communication. Some students also prioritize playing with their smartphones over talking and chatting with people they encounter. In the context of phubbing, the inability to be physically and emotionally present can lead to feelings of isolation. When individuals engage in phubbing, they are not fully present in social situations, both physically and emotionally. This disrupts social interactions, preventing them from creating an adequate interaction experience. This research uses a quantitative, associative approach. The variables in this study are phubbing behavior as the independent variable (X) and social interaction as the dependent variable (Y). The population in this study were 619 tenth and eleventh grade students of SMAN 1 Luhak Nan Duo. The sample size for this study was 243 students, selected using the Proportionate Stratified Random Sampling technique. The results of this study indicate that the simple linear regression test obtained the equation Y = 87.975 – 0.383X with a significance value of 0.000 < 0.05. Based on the categorization results, the phubbing behavior of class X and XI students at SMAN 1 Luhak Nan Duo is generally in the moderate category. This is indicated by a percentage of 43% with a total of 104 respondents and an average value (mean) of 85.27. Meanwhile, the results of the categorization of student social interactions also show that most are in the moderate category with a percentage of 46% and a total of 112 respondents. Thus, it can be concluded that both phubbing behavior and student social interactions are in the moderate category.